STUDENTS’ EXPERIENCES LEARNING ENGLISH VOCABULARY THROUGH GAMES IN INCREASING VOCABULARY MASTERY - Marida Nurul Azizah; Ine Rahayu Purnamaningsih (IKIP Siliwangi, 2023)
The advancement of technology is assisting humanity in several fields, including education. English is a global language, so learning English is vitally important. In addition, students must master four English skills in order to speak the language fluently: listening, speaking, reading, and writing. It is an irrefutable reality that the majority of students nowadays have access to new technologies that can be utilized at any time and in any location. This enables individuals to incorporate these technological advancements into their daily lives, particularly in the realm of education or learning. Using descriptive qualitative research done through interviews and tracing relevant literature, this research will answer the research question and be presented in a descriptive format. This research examined vocabulary instruction in vocational schools. The conclusion is that games can make learning English easy and fun for students. They can get a feel for words and phrases without having to remember them all by heart or get bored. Keywords: Students’ experiences; Learning; Vocabulary; Games